Analysis of the Individually Paying Program of the Philippine Health Insurance Corporation - Denise Valerie Silfverberg (Philippine Institute for Development Studies (PIDS), 2014)
The Individually Paying Program (IPP) is the voluntary component of the Philippines' social health insurance program. The program caters to those in the informal sector and those without a formal employer-employee relationship. Coverage levels for the IPP were found to be considerably low with a regional average of 57 percent and a provincial average of 53 percent. Massive variation between provinces was found. Four important factors were identified when looking into said variation. First, availability and accessibility is an issue. Second, substitution effect between private and public facilities was observed. Third, income levels do not appear to be a factor in determining the level of insurance coverage. Lastly, the size of certain sectors had a significant effect on the coverage levels observed in the province. Although there is a need to corroborate the findings with an individual-level analysis, these results are good indicators to start with in order to address the lack of coverage in the voluntary program of PhilHealth.
Keywords: 330; health care financing; Philippines; social health insurance; universal coverage; informal sector; voluntary program